Fluoride exposure and attention deficit hyperactivity disorder (ADHD) in Canadian youth - Riddell, Julia; Till, Christine (My University, 2022)
Fluoride was measured in urine and tap water. Youth (ages 6 to 17) or their parents completed a questionnaire asking about hyperactive and inattention symptoms and if the child has been diagnosed with ADHD. The researchers used statistical models to examine the relationship between fluoride exposure and ADHD diagnosis/symptoms.
Keywords: Children & Youth; Environment; Health; Society & Community